Expression of somatostatin receptors, angiogenesis and proliferation markers in pituitary adenomas: an immunohistochemical study with diagnostic and therapeutic implications (Swiss Medical Weekly, 2013)
PRINCIPLES: Pituitary adenomas are common intracranial neoplasms that generate symptoms as a result of either mass effect or the increased production of pituitary hormones. Although mostly benign, these tumours can be associated with considerable morbidity. We investigated a panel of immunohistochemical preparations to identify potential therapeutic targets and surrogate markers of clinical outcome. METHODS: Tumour tissue from 25 patients was evaluated for immunohistochemical expression of somatostatin receptors 1‒5, von Willebrand-factor (vWF), interleukin-8 (IL-8), vascular endothelial growth factor receptor 2 (VEGFR-2), kinesin spindle protein (Eg5) and MIB-1 (Ki-67), and its relationship with clinical features was analysed. RESULTS: The proliferation marker MIB-1 (Ki-67) was the only marker predictive of adenoma recurrence. Of note, 67% of all relapses were associated with tumours showing luteinising hormone expression. All pituitary adenomas showed variable somatostatin receptor, IL-8, Eg5, vWF and VEGFR-2 expression; a relationship between these parameters and clinical outcome could not be demonstrated in this cohort. CONCLUSIONS: This study validates MIB-1 (Ki-67) as a reliable marker of tumour recurrence in pituitary adenomas. Considering the consistently increased expression of Eg5, IL-8, VEGFR-2, somatostatin receptors and vWF in these tumours, further investigation as potential therapeutic targets is warranted.